Cost analyses of a web-based behavioral intervention to enhance fruit and vegetable consumption - McClure Jennifer B; Carlier Carola; Calvi Josephine H; Alexander Gwen; Ritzwoller Debra P; Sukhanova Anna; Rolnick Sharon; Johnson Christine (BMC, 2009)
Abstract Background The purpose of this paper is to evaluate costs associated with the online intervention trial, Making Effective Nutritional Choices for Cancer Prevention (MENU), and to connect the findings to the study outcomes. Methods Using prospective data collected during the MENU development and implementation phases, we estimated overall costs per person, incremental costs for the three arms of the MENU intervention, and incremental costs per change in fruit and vegetable (F&V) consumption across the studied population. The MENU study was conducted in five HMO sites of the Cancer Research Network. The number of eligible study participants who were enrolled in the study was 2,540. Recruited participants were randomized into (1) an untailored website program, (2) tailored website program, or (3) tailored web program plus personalized counseling (HOBI) via email. The primary measures for these analyses include the total intervention costs, average cost per participant, and the average cost per mean change in daily intake of F&V, stratified by study arm. Results The mean change in F&V consumption was greater in both the tailored arm and statistically higher in the HOBI arm relative to the untailored arm. The untailored arm achieved +2.34 servings increase vs. the tailored website arm (+2.68) and the HOBI arm (+2.80) servings increase. Total intervention costs for MENU participants who completed the 12-month follow-up assessment, by study arm, were estimated to be $197,197 or $110 respectively. This translates to $69 per participant in the untailored web site intervention, $81 per participant in the tailored website intervention, and $184 per participant in the HOBI intervention and a cost per average change in F&V consumption to be $35, $27 and $61 respectively. Conclusions Providing personalized "tailored" messages and additional personalized support via email generated an additional $12-$115 per participant, over the untailored web program. Incremental increases in F&V consumption associated with the email support arm were associated with considerable increases in intervention costs, suggesting that the most cost effective arm of the MENU study by servings gained was the tailored website.